ASB7 Is a Novel Regulator of Cytoskeletal Organization During Oocyte Maturation - Liu, Yuan; Li, Xiaoyan; He, Yongfu; Wang, Hengjie; Gao, Min; Han, Longsen; Qiu, Danhong; Ling, Li; Liu, Honglin; Gu, Ling (Frontiers in Cell and Developmental Biology, 2020)
Ankyrin repeat and SOCS box (ASB) family members have a C-terminal SOCS box and an N-terminal ankyrin-related sequence of variable repeats. To date, the roles of ASB family members remain largely unknown. In the present study, by employing knockdown analysis, we investigated the effects of ASB7 on mouse oocyte meiosis. We show that specific depletion of ASB7 disrupts maturational progression and meiotic apparatus. In particular, abnormal spindle, misaligned chromosomes, and loss of cortical actin cap are frequently observed in ASB7-abated oocytes. Consistent with this observation, incidence of aneuploidy is increased in these oocytes. Meanwhile, confocal scanning reveals that loss of ASB7 impairs kinetochore-microtubule interaction and provokes the spindle assembly checkpoint during oocyte meiosis. Furthermore, we find a significant reduction of ASB7 protein in oocytes from aged mice. Importantly, increasing ASB7 expression is capable of partially rescuing the maternal age-induced meiotic defects in oocytes. Together, our data identify ASB7 as a novel player in regulating cytoskeletal organization, and discover the potential effects of ASB7 on quality control of aging oocytes.